Mathematical Approach Of Q-Learning With Temporal Difference Method In Sensor Data Communication In Cloud Environment - et. al., P. Abirami, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Access to data is efficient and can be managed with minimal sensors. However the sensor data captured at different locations can be integrated to the cloud[11]In this work, we derived the optimum path, which is the shortest, and the time and power are optimized. We consider the network topologies where nodes and paths are assigned by a definite probability. The Bellman equation and the temporal difference method are used in Q-learning. Bellman -Temporal based algorithm is used for finding the optimal path among users in the cloud environment.